Tratamento de efluente de terminal de combustível coagulação/floculação/fotocatálise - Ferrari, Ana Maria Cristina da Cruz (2011)
The treatment systems of gas station wastewater (oil-water separator - OWS) has shown to be insufficient in reducing the organic matter, especially with concerns to aliphatic and aromatic hydrocarbons, major pollutants found in these effluents. In the end of 2009 the number of existing gas stations in Brazil was nearly 38,000, many of which offer, besides the fuel supply, services of oil changing, car wash and convenience stores. Many fuel stations discard their waste on public sewage systems, becoming potential polluters, adding to domestic sewage highly toxic and carcinogenic pollutants. Hence the need of developing systems those are effective in treating these effluents, and ensure the degradation of hydrocarbons and other pollutants. In this work, the efficiency of the combined treatment of gas station effluent by coagulation/flocculation/photocatalysis was investigated. The waste was collected from a gas station located in Maringá-PR, characterized and submitted to physico-chemical and photocatalytic treatments under VIS and UV radiation. The coagulants employed were Al2(SO4)3, FeCl3 and TANFLOC ® SG. Catalysts used were TiO2, ZnO and Nb2O5 calcined at 500 °C employed in the pure form and mechanical mixture (50%wt). The photocatalytic process was evaluated according to the reduction of absorbance, COD, turbidity and toxicity. The coagulation/flocculation with TANFLOC ® SG removed approximately 52% of TOC, 73% of COD and 97% of turbidity. The photocatalytic tests were carried out with the in natura and coagulation/flocculation clarified effluent, using VIS and UV radiation. The most active catalyst under VIS radiation was TiO2, reducing 43% of COD of in natura effluent and 53% of COD of clarified effluent. Under UV radiation, the best catalyst was the TiO2-ZnO, which reduced 45% of the COD of the in natura effluent and 67% of the COD of the effluent clarified. With combined treatment, it was possible to achieve treated water with COD of 104 mg/L, turbidity of 9.58 NTU and low toxicity to Artemia salina, and in some cases the elimination of toxicity was achieved.